2015
DOI: 10.1136/jfprhc-2015-101186
|View full text |Cite
|
Sign up to set email alerts
|

Giving information about the contraceptive implant using a DVD: is it acceptable and informative? A pilot randomised study

Abstract: The use of a DVD to provide patient information on Nexplanon is acceptable and informative, and may enhance patient consultations. A large randomised controlled trial may determine if provision of quality standardised information via DVD can improve uptake or continuation rates of long-acting reversible methods of contraception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
2
8
0
1
Order By: Relevance
“…The use of pre‐prepared scripts saves time and ensures consistent information; DVDs and web‐based information are becoming increasingly acceptable. Most women given information about the contraceptive implant using a DVD had knowledge recall as good as with a face‐to‐face consultation and found the DVD helpful and easy to understand . Women find contraceptive counseling acceptable during the abortion consultation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of pre‐prepared scripts saves time and ensures consistent information; DVDs and web‐based information are becoming increasingly acceptable. Most women given information about the contraceptive implant using a DVD had knowledge recall as good as with a face‐to‐face consultation and found the DVD helpful and easy to understand . Women find contraceptive counseling acceptable during the abortion consultation.…”
Section: Methodsmentioning
confidence: 99%
“…Most women given information about the contraceptive implant using a DVD had knowledge recall as good as with a face-to-face consultation and found the DVD helpful and easy to understand. 51 Women find contraceptive counseling acceptable during the abortion consultation. 47 Telephone counseling about contraception, separated from the abortion consultation, is an alternative model.…”
Section: Lessons For Improving Provision Of Contraception After Prementioning
confidence: 99%
“…AP ünitelerinin bekleme salonlarında, acil kontrasepsiyon, üreme sisteminin fizyolojisi, ovülasyon günlerinin belirlenmesi, geri çekme yönteminin daha etkili nasıl kullanılabileceği gibi üzerinde nispeten biraz daha az durulan konulara dair bilgi vermek için hazırlanmış video ya da broşür gibi görsel ve yazılı iletişim araçları farkındalığın artırılmasında iyi bir alternatif olabilir. 32 Diğer taraftan doğal AP yöntemleri kullanımı söz konusu olduğunda, acil kontrasepsiyona ilişkin bilgi sahibi olmak oldukça önemlidir. Çalışmamızda ise acil kontrasepsiyon hakkındaki bilginin, anlaşılmayacağı gerekçesiyle talep edilmedikçe verilmediği görülmektedir.…”
Section: Hemşi̇releri̇n Tutumlariunclassified
“…2 There is further evidence (from women requesting an abortion) that information on contraceptive methods can also be effectively delivered in an audiovisual format and that they feel more confident about the chosen contraceptive method than those who only discuss the method with a clinician (without seeing a video). 4 We developed an audiovisual animation of approximately 3 minutes' duration to provide core information about EMA. The content of this animation was based on guidance from Royal College of Obstetrics and Gynaecology (RCOG) 5 on what women need to know prior to attending an abortion clinic appointment, national guidelines in Sweden and France and the expert opinion of the multinational investigator team for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, abortion care providers have reported that women who have received information this way are better prepared and informed about what abortion involves, allowing consultations to progress more easily and greater time for discussion of future contraceptive methods 2 . There is further evidence (from women requesting an abortion) that information on contraceptive methods can also be effectively delivered in an audiovisual format and that they feel more confident about the chosen contraceptive method than those who only discuss the method with a clinician (without seeing a video) 4 …”
Section: Introductionmentioning
confidence: 99%